Profiles of Odd- and Branched-Chain Fatty Acids and Their Correlations With Rumen Fermentation Parameters, Microbial Protein Synthesis, and Bacterial Populations Based on Pure Carbohydrate Incubation in vitro - Xin, Hangshu; Khan, Nazir Ahmad; Liu, Xin; Jiang, Xin; Sun, Fang; Zhang, Shuzhi; Sun, Yukun; Zhang, Yonggen; Li, Xiang (Frontiers in Nutrition, 2021)
The objectives of this study were to evaluate changes in profiles of odd- and branched-chain fatty acids (OBCFA), including pentadecanoic acid (C15:0), 13-methyltetradecanoic acid (iso-C15:0), 12-methyltetradecanoic acid (anteiso-C15:0), 14-methylpentadecanoic acid (iso-C16:0), heptadecanoic acid (C17:0), 15-methylhexadecanoic acid (iso-C17:0), and 14-methylhexadecanoic acid (anteiso-C17:0) during in vitro fermentation of pure carbohydrates mixtures in the buffer-rumen fluid. The second objective was to correlate the changes in the OBCFA profile to the corresponding changes in ruminal fermentation parameters, microbial crude protein (MCP) synthesis, and bacterial populations. Five pure carbohydrates mixtures containing different cellulose: starch (C:S) ratios, i.e., 0:100, 25:75, 50:50, 75:25, and 100:0, were incubated for 6, 12, 18, and 24 h in vitro. The results showed that there was significant interaction (P < 0.05) between C:S and incubation time for changes in all OBCFA profiles, except iso-C17:0. The highest concentration of total OBCFA (3.94 mg/g dry matter; DM) was observed in the residues after 24 h of fermentation when the C:S was 0:100, while the lowest concentration of OBCFA (1.65 mg/g DM) was produced after 6 h of incubation when the C:S was 50:50. The correlation analysis revealed that the concentration of iso-C16:0 might be a potential marker for the estimation of total volatile fatty acids (ρ = 0.78) and MCP synthesis (ρ = 0.82) in the rumen. Compared to starch degrading bacteria, cellulolytic bacteria had stronger correlations with OBCFA concentrations, and the strongest correlation was found between the population of Ruminococcus flavefaciens with C15:0 concentration (ρ = 0.70). Notably, this is the first paper reporting relationship between OBCFA with rumen fermentation products and microbial protein synthesis based on fermentation of pure carbohydrates mixtures in vitro, and thus avoid confounding interference from dietary protein and fat presence in the in vivo studies. However, more in-depth experiments are needed to substantiate the current findings.